Adaptation of the material balance of a gas deposit - Zarubin, Yu.; Hunda, M.; Mamus, P. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2020)
The aim of the researching is to study the application of the material balance method with modern technologies to create a useful gas reservoir model with water influx. The basic equations of material balance are analyzed taking into account the Mendeleev-Clapeyron law for gases. The analysis was performed taking into account the water influx component according to Fetkovich's equations. The paper highlights the problems of identifying the parameters of the material balance model as material balance model doesn’t include the geological structure of deposits. The calculation was done by material balance models created on Mathcad and VBA Excel. The analysis and examples given in the article testify to the expediency of applying the method of material balance with VBA Excel to clarify gas reserves, including those with a water-driven or mixed mode of development and obtain an adequate model of the reservoir.